Lymphatic Drainage in Immediate Post-Operative Upper Limb Surgery (Research, Society and Development, 2021)
Introduction: Lymphatic drainage is a specialized massage technique which includes a set of maneuvers that aim to drain excess fluid accumulated in the interstitium. Manual lymphatic drainage is a technique which is performed for the best results during the immediate post-operative period of patients undergoing surgical procedures. It is not only used for aesthetic purposes but also for the prevention and treatment of pathologies. The present work aims to demonstrate the benefits of lymphatic drainage in the immediate post-operative period of upper limb surgery, reviewing the anatomy and physiology of the lymphatic system, verifying the effect of lymphatic drainage in reducing or eliminating pain and analyzing the effects of lymphatic drainage on edema. Objective: The objective main is to identify the importance of manual lymphatic drainage in post-operative treatment. Method: The research method was a literature review of scientific articles, DeCS and academic Google. Conclusion: o comply with the Manual Lymphatic Drainage in the upper limbs postoperatively, they provide effective and satisfactory results, with an excellent recovery, thus bringing an improvement in edema and hematoma and consequently reducing pain reported by most patients.